An Empirical Study to Analyse Indian Cricketers' Career Progression in View of Current Cricket Explosion. (May 2020) - Ray, Subhasis
Sports career is brief and sport career transition (SCT) is a well-researched topic to see how players deal with it. Cricket is the most popular sport in India and the game is evolving thick and fast. Cricket has become an all season sport barring rainy and snowy conditions. Plethora of options are now available to the players which includes test cricket, one day international (ODI), twenty 20 international (T20I), Indian Premier League (IPL) and similar franchise-based leagues on T20 and T10 along with first-class domestic cricket. With this deluge in cricket, it is pertinent to study career progression of cricketers. IPL, despite a brand value of US$6.3 billion, is often criticized for bringing players into limelight too soon, paving way for playing test matches and fading even sooner into oblivion being unable to cope with volume and variety of cricket. The present article analyses Indian cricketers' career progression pattern using hierarchical clustering analysis, and it also investigates if cricketers are graduating faster from domestic to test cricket using two-sample t -test.